Efi Avdela, Dimitris Arvanitakis, Eliza A. Delveroudi, Evgenios Matthiopoulos, Socrates Petmezas and Tassos Sakellaropoulos, eds., Φυλετικές θεωρίες στην Ελλάδα: Προσλήψεις και χρήσεις στις επιστήμες, την πολιτική, τη λογοτεχνία και την ιστορία της τέχνης κατά τον 19ο και τον 20ό αιώνα [Racial theories in Greece: perception and use in science, politics, literature and art history in the 19th and 20th centuries] - Hamilakis, Yannis (Historein, 2020)
Review of Efi Avdela, Dimitris Arvanitakis, Eliza Anna Delveroudi, Evgenios Matthiopoulos, Socrates Petmezas, and Tassos Sakellaropoulos, eds., Φυλετικές θεωρίες στην Ελλάδα: Προσλήψεις και χρήσεις στις επιστήμες, την πολιτική, τη λογοτεχνία και την ιστορία της τέχνης κατά τον 19ο και τον 20ό αιώνα [Racial theories in Greece: perception and use in science, politics, literature and art history in the 19th and 20th centuries]. Irakleio: Crete University Press and Philosophy School of the University of Crete Press, 2017. 520 pp.